The Behavior of Generations ‘’Y’’ and ‘’Z’’ in Seeking Information as a Source of Knowledge in the iJogja Library - MOHAMAD PANDU RISTIYONO (CV KULTURA DIGITAL MEDIA, 2022)
The purpose of this study was to determine the behavior of generations Y and Z of iJogja digital library users in utilizing digital collections as a source of information. This research method is descriptive with a qualitative approach. There were seven informants in this study and data collection techniques used interviews and literature studies and data analysis techniques used Miles and Huberman data analysis techniques. The results of this study in terms of needs can be classified into two dominant types of needs, namely achievement needs and power needs. While the impetus that arises in the use of digital libraries is divided into two, namely intrinsic and extrinsic. Intrinsic encouragement in this research comes from oneself such as utilizing the library's functions, answering curiosity and increasing knowledge. While extrinsic encouragement is getting information from friends and social media as well as academic environmental factors.